2015
DOI: 10.1016/j.compedu.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

What are the educational affordances of wearable technologies?

Abstract: a b s t r a c tBy providing users with hands-free access to contextually relevant knowledge, wearable technologies are poised to inspire a new generation of mobile learning design. However, in order for educators to harness the pedagogical opportunities of wearable technologies it is crucial for them to develop an understanding of their potentials, or 'affordances'. This paper analysed the perceptions of 66 educators from around the world who self-rated as having a 'good' or 'very good' understanding of wearab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
110
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(111 citation statements)
references
References 28 publications
0
110
0
1
Order By: Relevance
“…This was highlighted by Bower and Sturman (2015) who showed that mobile simulation solutions are a useful pedagogical technology. Analysing the participant feedback in detail, showed that 75% of students indicated via the survey that they "found the use of multiple forms of media (3DP and app) effective".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was highlighted by Bower and Sturman (2015) who showed that mobile simulation solutions are a useful pedagogical technology. Analysing the participant feedback in detail, showed that 75% of students indicated via the survey that they "found the use of multiple forms of media (3DP and app) effective".…”
Section: Discussionmentioning
confidence: 99%
“…Bower and Sturman (2015) reviewed the affordances of these technologies and noted that simulation was a useful pedagogical affordance of this technology, with engagement also featuring prominently in their review. However, they also noted participants highlighted cost and processing power as issues with this technology.…”
Section: Mixed Reality For Simulation and Skills Trainingmentioning
confidence: 99%
“…Researchers in the field have primarily focused on handheld devices such as smartphones and tablets but have paid less attention to various wearable technologies such as smart glasses and smartwatches. Wearables are "technologies as embodied companions that become extensions of the self" [22]. The emergence of wearables within ML has been influenced by developments related to the Internet of Things.…”
Section: Mobile Learningmentioning
confidence: 99%
“…These studies however did not test user experience. Bower and Sturman (2015) examined the potential of wearable technologies, where they identified affordances such as experiencing various scenarios that otherwise would be risky or not possible (e.g. a tour in a medieval village, zooming in), raising involvement and engagement, communication, realtime guidance, feedback, and gamification.…”
Section: Related Workmentioning
confidence: 99%